Issues bordering the French language in Sub-Saharan Africa: Nigeria as a case study - FAUSTINA AREMU (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: Nigeria is a country in South Saharan Africa, and this study looked into questions concerning the French language used there. Some of the reasons why the French language may or may not have become widely spoken in certain African countries, particularly Nigeria, are discussed.Method: To accomplish this, a qualitative method was employed.Findings: The findings suggest that, alongside other issues, focusing on psycho-pedagogical issues is the most effective way to address the issues highlighted in this paper. Making French mandatory in all levels of education, especially in public schools in Nigeria, is the best way to ensure the survival of French in Sub-Saharan Africa, especially in Anglophone Africa. In light of the arguments made in this paper, the French language across all disciplines should be reconsidered, with special attention paid to its role in Nigeria’s public school system.Implications/Novel Contribution: The purpose of this paper is to examine Nigeria as a case study of a borderland language in Sub-Saharan Africa, specifically in West Africa. This demonstrated that one of the major factors working against the survival of the English language in Sub-Saharan Africa is the widespread lack of recognition and appreciation for it, especially in the English-speaking countries of the region.